Climate-Smart Crop-Livestock-Aquaculture Integration Course Module - Djagoun, Chabi; Rukarwa, Runyararo Jolyn; Sorho, Fatogoma (2024)
This module aims to develop knowledge and understanding of agriculture as a dynamic and interactive system that uses crops, animals and fishes to produce food for livelihood improvement. At the end of the course, students are able to apply principles of climate-smart agriculture to improve the sustainability of crop-livestock–aquaculture systems; understand a case study of integrated farming systems and come up with their own observations, criticisms and probable ways of improving the system; assess environmental health risks from a crop-aquaculture-livestock integrated system; advise on the management of social-economic and environmental challenges pertaining to the crop-livestock–aquaculture systems.